Achieving Successful Outcomes in High-Level Athletes With Borderline Hip Dysplasia Undergoing Hip Arthroscopy With Capsular Plication and Labral Preservation: A Propensity-Matched Controlled Study. Issue 9 (July 2021) - Jimenez, Andrew E.; Monahan, Peter F.; Miecznikowski, Kara B.; Saks, Benjamin R.; Ankem, Hari K.; Sabetian, Payam W.; Lall, Ajay C.; Domb, Benjamin G.
Background: Return to sports (RTS) rates and patient-reported outcomes (PROs) after hip arthroscopy in athletes with borderline dysplasia (BD) have not been established. Purpose: (1) To report minimum 2-year PROs and RTS rates in high-level athletes with BD who underwent hip arthroscopy for labral pathology in the setting of microinstability and (2) to compare clinical results with those of a matched control group of athletes with normal acetabular coverage. Study Design: Cohort study; Level of evidence, 3. Methods: Data were reviewed for surgery performed between January 2012 and July 2018. Patients were considered eligible if they received a primary hip arthroscopy in the setting of BD (lateral center-edge angle, 18°-25°) and competed in professional, collegiate, or high school sports. Inclusion criteria included preoperative and minimum 2-year follow-up scores for the modified Harris Hip Score, Non-arthritic Hip Score, Hip Outcome Score–Sport Specific Subscale, and visual analog scale for pain. Athletes with BD were matched to a control group of athletes with normal acetabular coverage (lateral center-edge angle, 25°-40°). Results: A total of 65 patients with BD were included in the study with a mean ± standard deviation follow-up of 47.5 ± 20.4 months. Athletes with BD showed significant improvement in all outcome measures recorded, demonstrated high RTS rates (80.7%), and achieved the minimal clinically important difference (MCID) and Patient Acceptable Symptom State (PASS) for the Hip Outcome Score–Sport Specific Subscale at high rates (MCID, 90.8%; PASS, 75.4%). When compared with a propensity-matched control group with normal acetabular coverage, capsular plication was performed more commonly in the BD group (93.8% vs 82.7%; P = .037). PROs and RTS, PASS, and MCID rates were similar between the BD and control groups ( P > .05). Conclusion: High-level athletes with BD who undergo primary hip arthroscopy for labral pathology in the setting of microinstability may expect favorable PROs and RTS rates at minimum 2-year follow-up. These results were comparable with those of a control group of athletes with normal coverage.